Development and Validation of a Questionnaire to Measure Psychosocial Work Stressors in Modern Working Environments. Issue 3 (March 2020) - Diebig, Mathias; Dragano, Nico; Körner, Ulrike; Lunau, Thorsten; Wulf, Ines Catharina; Angerer, Peter
Abstract : Objective: The rapid development of technology is changing working conditions of many employees. With this, appropriate measurement instruments to capture work-related psychosocial risks to create healthy working conditions are becoming more and more important. Therefore, we developed and validated a questionnaire to assess stressors in work settings which are characterized by a high degree of digitization. Method: The validation was based on two independent studies with data collected in four subsamples. All participants were asked about their working conditions and health-related topics using online questionnaires. Results: The resulting 16-item questionnaire consists of five scales: work load, boundary permeability, participation, leader support, and usability. Conclusions: The results show that the five identified stressors showed acceptable to good values with regard to reliability (internal consistencies, test-retest reliabilities, and interrater agreement) as well as (convergent and concurrent) validity.